Pengaruh Metode Two Stay Two Stray (TSTS) terhadap Hasil Belajar IPAS Siswa Kelas IV SD Negeri 2 Margadadi Lampung Selatan - Anggraini, Diah Anggraini; Nurul Hidayah; Yudesta Erfayliana (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study aims to examine the effect of the Two Stay Two Stray (TSTS) learning method on the IPAS learning outcomes of fourth-grade students at SD Negeri 2 Margadadi, Jati Agung District, South Lampung. The study was conducted to address the need for more interactive learning methods that can improve students’ understanding and achievement in IPAS learning. Design/methods – This study employed a quantitative approach with a quasi-experimental design using the Nonequivalent Control Group Design. The sample consisted of class IV B as the experimental class and class IV A as the control class, selected through cluster random sampling. Data were collected using multiple-choice learning outcome tests administered as pretest and posttest. The data were analyzed through normality tests, homogeneity tests, and an independent sample t-test using SPSS. Findings – The findings show that the posttest mean score of the experimental class was 91.71, while the control class obtained a mean score of 83.81. The independent sample t-test result showed a significance value of 0.002 < 0.05, indicating a significant difference between the two classes. Therefore, the Two Stay Two Stray (TSTS) learning method has a significant effect on improving students’ IPAS learning outcomes in fourth grade at SD Negeri 2 Margadadi, Jati Agung District, South Lampung.